2016
DOI: 10.1016/j.seizure.2016.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Automated seizure detection systems and their effectiveness for each type of seizure

Abstract: Epilepsy affects almost 1% of the population and most of the approximately 20-30% of patients with refractory epilepsy have one or more seizures per month. Seizure detection devices allow an objective assessment of seizure frequency and a treatment tailored to the individual patient. A rapid recognition and treatment of seizures through closed-loop systems could potentially decrease morbidity and mortality in epilepsy. However, no single detection device can detect all seizure types. Therefore, the choice of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
173
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(179 citation statements)
references
References 132 publications
1
173
0
5
Order By: Relevance
“…The EDA might also help detect and characterize seizures with subtle or no motor movement. A recent review suggests that the EDA signal is one of the most promising alternatives for a widespread variety of epileptic episodes 24 . A study with an Empatica E3 wristband reported that 97% of 34 predominantly non-motor seizures could be detected with a hierarchical classifier based on EDA 36 .…”
Section: Limits and Future Workmentioning
confidence: 99%
“…The EDA might also help detect and characterize seizures with subtle or no motor movement. A recent review suggests that the EDA signal is one of the most promising alternatives for a widespread variety of epileptic episodes 24 . A study with an Empatica E3 wristband reported that 97% of 34 predominantly non-motor seizures could be detected with a hierarchical classifier based on EDA 36 .…”
Section: Limits and Future Workmentioning
confidence: 99%
“…18,28,29 To evaluate semiology, movements can be analyzed using accelerometry, surface electromyography, video detection systems, mattress sensor, and seizure-alert dogs; physiological signals can be evaluated by electrocardiography, skin temperature, audio classification, and respiratory rate changes techniques. The evaluation of the manifestation of epilepsy is vital to defining the accurate monitoring and treatment procedure.…”
Section: Traditional Approaches To Automatic Epilepsy Evaluationmentioning
confidence: 99%
“…The evaluation of the manifestation of epilepsy is vital to defining the accurate monitoring and treatment procedure. 18 The success of epilepsy evaluation relies especially on evaluating the electroclinical correlation, which allows the SEEG technique, by analyzing the clinical signs recorded by video monitoring and the electrical activity registered by depth electrodes. 18,28,29 To evaluate semiology, movements can be analyzed using accelerometry, surface electromyography, video detection systems, mattress sensor, and seizure-alert dogs; physiological signals can be evaluated by electrocardiography, skin temperature, audio classification, and respiratory rate changes techniques.…”
Section: Traditional Approaches To Automatic Epilepsy Evaluationmentioning
confidence: 99%
“…EEG aside, different biometric signals have been proposed for detecting the epileptic seizures [10,33]: gyroscopes, magnetometers, implanted advisory system, electromyography, ECG, ACM, video detection systems, mattress sensor, and audio classification. BSN placed on the body together with MCC has been proposed for epilepsy detection in [8]; more specifically, the BSN includes an ACM cap, a wrist band including a temperature sensor and an ACM, a moisture sensor, and microphone.…”
Section: Introductionmentioning
confidence: 99%